Nutrition and Sarcopenia: A Review of the Evidence and Implications for Preventive Strategies - Siân Robinson; Cyrus Cooper; Avan Aihie Sayer (Journal of Aging Research)
Prevention of age-related losses in muscle mass and strength is key to protecting physical capability in older age and enabling independent living. To develop preventive strategies, a better understanding is needed of the lifestyle factors that influence sarcopenia and the mechanisms involved. Existing evidence indicates the potential importance of diets of adequate quality, to ensure sufficient intakes of protein, vitamin D, and antioxidant nutrients. Although much of this evidence is observational, the prevalence of low nutrient intakes and poor status among older adults make this a current concern. However, as muscle mass and strength in later life are a reflection of both the rate of muscle loss and the peak attained in early life, efforts to prevent sarcopenia also need to consider diet across the lifecourse and the potential effectiveness of early interventions. Optimising diet and nutrition throughout life may be key to preventing sarcopenia and promoting physical capability in older age.